Using Bayesian approach to optimize some Microbiology data - Hossain, Ahmed (BRAC University, 2010)
The main purpose of this paper is to use Bayesian technique for identifying the conditions under which the bacteria growth is optimal. Such kind of analysis is important in microbiology when bacteria need culture in an optimum manner, so they can be identified, before adequate antibiotics can be developed. The dataset was collected under three different conditions which can be found in Binnie (2004). Therefore our interest lies in investigating how these three covariates are affecting the measurements of Bacteria count.